Is Wrestling a Promising Sport for Youngsters from Deprived Regions? - Celal Taşkıran; Mehmet Kutlu; Erkan Demirkan; Turgut Yıldırım (Central European Journal of Sport Sciences and Medicine)
This study aimed at exploring the social factors in lead young wrestlers with disadvantaged background and from deprived regions to take up wrestling. Utilizing a cross-sectional survey design, the research explores demographics, socioeconomic status, and the motivators behind wrestling involvement among 129 participants aged 9 to 16. Purposefully selecting regions with limited wrestling activity, the study is part of a special project. Conducted incentive camping period in Antalya study reveal that key motivators to wrestlers include Physical Education Teachers (PET) (22%), friends (19%), siblings (15%), fathers (12%) and others (14%). Although, there were 70% of participants who have some idols from countrywide, it was found that they have lack of idols in the regions of our participant group. Despite wrestlers have some disadvantages in social status such as the lack of wrestling authority in family members, camping affected them positively and encouraged them in wrestling career. Prospective wrestlers had declared that they come from low-income families underlining the socio-economic difficulties. It is thought that situations such as conducting the study in a seaside camp in a 5-star hotel, recognizing idol athletes increase the children’s interest in wrestling and will have a positive effect on their future sports life despite their disadvantaged backgrounds